2022
DOI: 10.36312/jolls.v2i2.763
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Prototype of Picture-Based Learning Materials in the Teaching of Speaking Skills

Abstract: Various pictures can be utilized as learning media to facilitate language learners to learn vocabulary, pronunciation, grammar, and speaking skills. In the teaching of speaking, serial pictures can be designed to promote students to speak what the pictures illustrate. Therefore, speaking skills become crucial part in learning the target language. In  learning English where learners have limited sources to access real English communication with native or non-native English speakers, speaking materials become es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Our study found that frontal alpha asymmetry was highly correlated with language learners' enjoyment of poetry, thus filling the gap in this area to some extent. Third, pictures as one of the important visual materials in foreign language classrooms (Tuttle, 1975 ; Hafidz Zaid, 2020 ; Kumar, 2021 ) play a part in language learning (Bush, 2007 ; Pratiwi and Ayu, 2020 ; Karya et al, 2022 ). Based on previous findings, the current study has shown that the effect caused by different styles of pictures is related to language learner's proficiency level, which is in line with the results of existing studies examining the effect of pictures on language learning.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that frontal alpha asymmetry was highly correlated with language learners' enjoyment of poetry, thus filling the gap in this area to some extent. Third, pictures as one of the important visual materials in foreign language classrooms (Tuttle, 1975 ; Hafidz Zaid, 2020 ; Kumar, 2021 ) play a part in language learning (Bush, 2007 ; Pratiwi and Ayu, 2020 ; Karya et al, 2022 ). Based on previous findings, the current study has shown that the effect caused by different styles of pictures is related to language learner's proficiency level, which is in line with the results of existing studies examining the effect of pictures on language learning.…”
Section: Discussionmentioning
confidence: 99%
“…They "posted the answer sheets on the YouTube comment column. They also got excellent results from doing assignments based on the explanation from the YouTube video" (Adisti, 2022;Karya et al, 2022). Meanwhile, Chhabra (2012) claimed that "YouTube videos can be used in an ELT classroom for various aspects of English as to enhance vocabulary, accents, pronunciations, voice modulation and many more (3)."…”
Section: Introductionmentioning
confidence: 99%
“…It mean that students need to teach how to develop their skills in order to solve the problems in their daily life activities, not memorise the concept over all. In principle learning, teaching materials is applied to encourage students to develop critical thinking, collaboration, creativity, and communication (Karya et al, 2022;Habibi et al, 2022). According to the research results from the OECD obtained three dimensions of learning, namely information, communication, ethics, and social influence (Ananiadou & Claro, 2009).…”
Section: Introductionmentioning
confidence: 99%